Evaluation of Electric Energy Losses in Kirkuk Distribution Electric System Area - ., Sameer S. Mustafa; Yasen, Mohammed H.; Abdullah, Hussein H.; Hazaa, Hadi K. (Iraqi Journal for Electrical and Electronic Engineering, 2011)
Correct calculations of losses are important for several reasons. There are two basic methods that can be used to calculate technical energy losses, a method based on subtraction of metered energy purchased and metered energy sold to customers and a method based on modeling losses in individual components of the system. For considering the technical loss in distribution system included: transmission line losses, power transformer losses, distribution line losses and low-voltage transformer losses. This work presents an evaluation of the power losses in Kirkuk electric distribution system area and submit proposals and appropriate solutions and suggestions to reduce the losses . A program under Visual Basic was designed to calculate and evaluate electrical energy losses in electrical power systems.